Reduction of COD, pH and Phosphate Levels in Laundry Wastewater Using Multi Soil Layering (MSL) Method - Aster Rahayu; Maryudi Maryudi; Nuraini Nuraini; Nafira Alfi Zaini Amrillah; Irwan Mulyadi; Farah Fadillah Hanum (Universitas Nusa Bangsa, 2023)
The growth of laundry services is directly proportional to the use of detergent. Detergent is a cleaning product that contains high levels of COD and phosphate. One method that can be used to overcome this problem is Multi Soil Layering (MSL). This research focussed on the flow rate's effect on decreasing pH, COD, and phosphate levels in industrial laundry waste. MSL was installed using a mixture of andosol soil and activated charcoal from coconut shells. Laundry wastewater was let into MSL with flowrate: 10, 50, and 100 ml/minute. The waste degradation system is placed anaerobically by optimising the anaerobic process in the andosol soil. The pH, COD, and phosphate levels were achieved at 7, 90.9%, and 80.7% by draining the laundry industry waste into the MSL system. This MSL method has a residence time of 266 minutes for a flowrate of 100 mL/minute, 532 minutes for a flowrate of 50 mL/minute and 2660 for a flowrate of 10 mL/minute. Keywords: MSL; Phosphate; COD; Laundry Industry; Andosol soilABSTRAKPenurunan Kadar COD, pH dan Fosfat pada Air Limbah Laundry Menggunakan Metode Multi Soil Layering (MSL)Pertumbuhan jasa laundry berbanding lurus dengan penggunaan detergen. Detergen merupakan produk pembersih yang mengandung COD dan fosfat dalam kadar tinggi. Salah satu cara yang dapat digunakan untuk mengatasi masalah tersebut adalah Multi Soil Layering (MSL). Penelitian ini berfokus pada pengaruh laju alir terhadap penurunan pH, COD, dan kadar fosfat pada limbah laundry industri. MSL dipasang menggunakan campuran tanah andosol dan arang aktif dari tempurung kelapa. Air limbah laundry dimasukkan ke dalam MSL dengan debit aliran: 10, 50, dan 100 mL/menit. Sistem degradasi sampah ditempatkan secara anaerobik dengan mengoptimalkan proses anaerobik di tanah andosol. Kadar pH, COD, dan fosfat dicapai pada 7, 90,9%, dan 80,7% dengan mengalirkan limbah industri laundry ke dalam sistem MSL. Metode MSL ini memiliki waktu tinggal 266 menit untuk laju alir 100 mL/menit, 532 menit untuk laju alir 50 mL/menit dan 2660 untuk laju alir 10 mL/menit.Kata kunci: MSL; Fosfat; COD; Industri Laundry; Tanah Andosol